Paederus dermatitis: An observational study (Annals of Medical Research, 2021)
None
Keywords: key. Clinical and demographical features of all the cases were retrospectively reviewed.br /Results: A total of 44 patients were enrolled in the study. The mean age of the patients was 25.2 years. The disease peaked in August and September. The most common localization was head-neck region. On the dermatologic examination, three main clinical patterns were observed: dermatitis linearis (n=31, 70.4%), localized pustular dermatosis (n=4, 9%) and kissing dermatitis (n=7, 15.9%). Two (4.54%) cases showed a combination of two patterns. Three cases (6.8%) had periorbital involvement.br /Conclusion: Paederus dermatitis is a form of irritant contact dermatitis which can easily be misdiagnosed. Awareness about the clinical patterns of the disease and its typical features is essential for true diagnosis and management.br / Contact Dermatitis; Dermatitis Linearis; Irritant Dermatitis; Paederus Dermatitis.